Kepatuhan Santri Terhadap Aturan di Pondok Pesantren Modern - Rahmawati, Anita, Dr. Sri Lestari, S.Psi.,M.Si (2015)
In the boarding school students are faced a number of rules which should be obeyed and different with the school in general. The regulations that applied include the code of conduct related academic activities as well as the code of conduct that governs daily activities. The purpose of this study is to understand and describe the students compliance with the rules in modern boarding school. Qualitative methods used in this study, which involved 130 students in Modern Islamic Boarding School Assalam Sukoharjo consists of 58 students male and 72 female students, including 1st grade, 2nd and 3rd grade Madrasah Tsanawiyah (MTs). Collecting data using open ended questionere and interview. The results show that student compliance to the rules influenced by internal factors such as self-awareness, responsibility, moral reasoning and self-control, and external factors such as behavior of peers, exemplary teachers, exemplary organization of school administrators, enforcement of rules and punishment. Teachers who are able to enforce the rules consistenly and the organization of school administrators who are able to serve as an example or be a role model to students can support compliance with the rules, while teachers are unfair in enforcing the rules and organization of school administrators who are unable to comply with the rules made make students violating rules. Students who are able to show the compliance to the rules, they are able to understand the values of obedience and discipline to control the action of opposed the rules. The types of violations that student most often do is a violation of the language section, security section, ta'lim section and student section.